The The contemporaneity of Giordano Bruno - Novello, Mario (Cadernos de Astronomia, 2022)
This text is the result of an invitation made by Núcleo Cosmo-ufes to prof. Mário Novello to open the presentation of the film Giordano Bruno, by Giuliano Montalde, held at UFES on July 29, 2022. Prof. Novello gave a lecture before the screening of the film, expressing his views on Giordano Bruno's contribution to modern cosmology.
Keywords: Giordano Bruno; cosmology